MILITARY EXPENDITURE AND MACROECONOMIC PERFROMANCE – THE CASE OF AN EMERGING COUNTRY - OLOGBENLA, Patrick (Studia Universitatis Babeș-Bolyai Oeconomica, 2020)
The study investigates the nexus between military expenditure and macroeconomic performance in Nigeria between 1980 and 2017. Data on military expenditure and some macroeconomic variables such as output (GDP), exchange rate and inflation rate are used in the study. The Vector Auto-regression technique VAR is applied so as to study the interactions among the variables in the short run. The result shows that military expenditure in Nigeria is significantly influenced by output and exchange rate shocks. It was also revealed that military expenditure does not make significant contributions to the behaviour of output in Nigeria. Military expenditure appears to be insulated against inflation shock since the largest chunk of military expenditure is traded in foreign currency hence less affected by domestic prices. JEL classification: H19, H50, E00, E02;